Effect of Temperature on the Growth Rate of Carbon Nanotubes (CNTs) using Electrodeposition Method - Prabowo, Agung; Andoko, Andoko; Suryanto, Heru; Prasetya, Riduwan (TRANSMISI, 2024)
Electrodeposition is one of the carbon capture methods used to produce carbon nanotubes with temperature as one of the variable. The research aims to analyze the effect of temperature on the growth rate of carbon nanotubes of 723oC, 750oC, 800oC, 850oC and 900oC using X-Ray Diffraction (XRD) testing. Analyzing deposit morphology at the same temperature using Scanning Electron Microscope (SEM) testing. The results of research show that the most optimal growth rate for carbon nanotubes occurred at 750oC of 7,949 g cm-2 hours-1. At a temperature of 750oC, carbon deposits are easier than at 723oC because that’s the melting point of lithium carbonate and has not completely decomposed. The XRD test show that at 750oC is the highest peak at 2θ= 26.21o. The SEM test show that the optimal morphological structure formed occurs at a temperature variation of 750oC with a fibrous morphology and little impurity at the ends. The results of the CNT percentage using the Material Analysis Using Diffraction (MAUD) method show that the largest quantitative value of the CNT percentage occurs at a temperature of 800oC of 4.08%.